Extracellular Vesicle Therapy for Type 1 Diabetes - Soltani, Setareh; Mansouri, Kamran; Emami Aleagha, Mohammad Sajad; Moasefi, Narges; Yavari, Niloofar; Shakouri, Seyed Kazem; Notararigo, Sara; Shojaeian, Ali; Pociot, Flemming; Yarani, Reza (Frontiers in Immunology, 2022)
Type 1 diabetes (T1D) is a chronic disorder characterized by immune-mediated destruction of pancreatic insulin-producing β-cells. The primary treatment for T1D is multiple daily insulin injections to control blood sugar levels. Cell-free delivery packets with therapeutic properties, extracellular vesicles (EVs), mainly from stem cells, have recently gained considerable attention for disease treatments. EVs provide a great potential to treat T1D ascribed to their regenerative, anti-inflammatory, and immunomodulatory effects. Here, we summarize the latest EV applications for T1D treatment and highlight opportunities for further investigation.